KARAKTERISASI Bacillus sp. PENGHASIL ASAM INDOL ASETAT ASAL RIZOSFER PERTANIAN PASANG SURUT DAN POTENSINYA SEBAGAI PEMACU PERTUMBUHAN PADI LOKAL - Adistya Adistya; Hasrul Satria Nur; Yusriadi Yusriadi (Universitas Lambung Mangkurat, 2024)
Bacillus sp., a member of the microbe, resided in the rhizosphere, potentially in plant growth promoting through a direct or indirect mechanism - phytohormone production, i.e., ethylene, gibberellin, cytokinin, and indole acetic acid. Bacillus sp. from soil agriculture in tidal swamp lands was isolated. Morphological, biochemical, and physiological properties have characterized attributes of isolation. In addition, indole acetic acid production is detected using the colorimeter method with the Salkowski reagent. The capability of the isolate to regulate plant growth promotion was carried out by detecting the performance of the paddy plant on the Yoshida medium cultivated. Five isolates have been characterized as plant growth-promoting rhizobacteria, e.g., BML-1, KK, SLC-2, SLK, and SPBKK-1. Furthermore, five isolates showed differences in indole acetic acid production, with or without adding tryptophane as a precursor. Indole acetic acid production without tryptophane ranged from 0.364 – 7.046 mg.ml-1. On the other hand, the indole acetic acid production by adding tryptophane in varied concentrations, viz 1, 2, and 5 mg.ml-1 is respectively delineated as follows 0.819 – 8.227 mg.ml-1; 1.046 – 10.727 mg.ml-1; 1.954 -18.909 mg.ml-1. Meanwhile, the inoculation of Bacillus sp. isolates improved paddy plant growth regarding yield and root fibers of paddy plants.